KOMPARASI GEJALA DAMPAK STRES DAN MOTIVASI TERHADAP PRODUKTIVITAS WORK FROM HOME DAN WORK FROM OFFICE - Ihda Salma Sakina (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2023)
This research aims to determine the effect of stress symptom and motivation on perceived productivity work from home and work from office as a new company culture. This research approaches associative and quantitative with a sample of 114 respondents. The results shows on work from office if the stress symptom variable is high, perceived productivity is low. Furthermore, stress symptoms on work from the office are less than stress symptoms on work from home. Besides it, if the motivation variable increases, perceived productivity will also increase, while motivation on work from the office is higher than motivation on work from home. The results of the study show that the hypothesis can be accepted.